PELINDUNGAN HUKUM MEREK TERKENAL PUMA TERHADAP PEMBONCENGAN REPUTASI (PASSING OFF) OLEH MEREK PUMADA DIKAITKAN DENGAN PENERAPAN ASAS ITIKAD BAIK (ANALISIS PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NO. 10/PDT.SUS.MEREK/2020/PN.NIAGAJKT.PST.) - Olivia Laksmono; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2020)
The multitude benefits of trademark in the course of commercial activity, especially for well-known trademarks often attracts ill-intentioned parties to use trademarks that are similar to trademarks that are already well-known in order to pass off their products as if belonging or has relation to the well-known trademark. One instance is the local trademark PUMADA passing off their own products as of the well-known trademark PUMA’s by using similar name and logo in their trademark. In accordance with the practice of good faith in trademark registration as stipulated in Article 21 paragraph (3) Law No. 20 of 2016 concerning Trademarks and Geographical Indications, the registration of the local trademark PUMADA should have been rejected. However, in reality the registration was actually accepted by the Directorate of Trademarks and Geographical Indication who’s responsible for the registration of trademark in Indonesia. Hence, raising the question as to whether the local trademark PUMADA has indeed pass offed its products as of the well-known trademark PUMA’s and how’s the legal protection for the well-known trademark PUMA against such act of passing off by the local trademark PUMADA in relation to the practice of good faith. This research was conducted using normative legal research method, and reveals that the local trademark PUMADA has indeed pass offed its products as of the well-known trademark PUMA’s and the legal protection for the well-known trademark PUMA against such act of passing off by the local trademark PUMADA can be found in the regulations, but unfortunately not in practice.